Ecological Photodynamic Therapy: New trend to disrupt the intricate networks within tumor ecosystem - Rumie Vittar, Natalia Belen (2012)
As with natural ecosystems, species within the tumor microenvironment are connected by pairwise interactions (e.g. mutualism, predation) leading to a strong interdependence of different populations on each other. In this review we have identified the ecological roles played by each non-neoplastic population (macrophages, endothelial cells, fibroblasts) and other abiotic components (oxygen, extracellular matrix) directly involved with neoplastic development. A way to alter an ecosystem is to affect other species within the environment that are supporting the growth and survival of the species of interest, here the tumor cells; thus, some features of ecological systems could be exploited for cancer therapy. We propose a well-known antitumor therapy called photodynamic therapy (PDT) as a novel modulator of ecological interactions. We refer to this as “ecological photodynamic therapy.” The main goal of this new strategy is the improvement of therapeutic efficiency through the disruption of ecological networks with the aim of destroying the tumor ecosystem. It is therefore necessary to identify those interactions from which tumor cells get benefit and those by which it is impaired, and then design multitargeted combined photodynamic regimes in order to orchestrate non-neoplastic populations against their neoplastic counterpart. Thus, conceiving the tumor as an ecological system opens avenues for novel approaches on treatment strategies.